Coordinated species importation policies are needed to reduce serious invasions globally: The case of alien bumblebees in South America - Aizen, Marcelo Adrian (2019)
The global trade of species promotes diverse human activities but also facilitates the introduction of potentially invasive species into new environments. As species ignore national boundaries, unilateral national decisions concerning species trade set the stage for transnational species invasion with significant conservation, economic and political consequences. The need for a coordinated approach to species importation policies is demonstrated by the introduction of two bumblebee species into Chile for crop pollination, despite Argentina banning commercial importation of alien bumblebees based on expert opinion. The large garden bumblebee, Bombus ruderatus, was first introduced in 1982, and the buff‐tailed bumblebee, Bombus terrestris, has been continually introduced since 1997 as part of the burgeoning bumblebee trade. Both species have subsequently invaded southern South America. Today, the consequences of the growth of the bumblebee trade for agricultural pollination ranks among the top 15 emerging environmental issues likely to affect global diversity. Documented impacts of these invasions include the severe decline and local extinctions of the sole native Patagonian bumblebee, Bombus dahlbomii, pathogen transmission, flower damage and nectar robbing of native and cultivated plants. Policy implications. The South American bumblebee invasions portrayed here should alert governments to the unintended consequences of the booming international bee trade. More broadly, this case demonstrates that one country's importation decisions can have policy implications for its neighbours without consultation. Regrettably, coordinated international measures to prevent species invasions are seldom considered in South America or elsewhere, despite existing legal frameworks. The bumblebee case and others provide stark evidence of the pressing need for coordinated specific and general international policies concerning global species trade and their implementation.